Dinuclear Nitrato Coordination Compounds with Bis(3, 5‐tert‐butylpyrazol‐1‐yl)acetate. Issue 22 (8th July 2015) - Kozlevčar, Bojan; Jakomin, Klemen; Počkaj, Marta; Jagličić, Zvonko; Beyer, Andreas; Burzlaff, Nicolai; Kitanovski, Nives
Abstract: Two dinuclear centrosymmetric coordination compounds with the bis(3, 5‐di‐ tert ‐butylpyrazol‐1‐yl)acetic acid anion (L – = bd t bpza), namely, violet [Co(bd t bpza)(NO3 )]2 (1 ) and turquoise [Cu(bd t bpza)(NO3 )]2 (2 ), are reported. Around each metal(II) ion, the L – ligand is κ 3 ‐ N, N, O coordinated, and the M–O bonds are significantly longer than both M–N bonds. The coordination sphere is completed by short nitrato and M–O bonds to a ligand that is already κ 3 ‐ N, N, O coordinated to the adjacent intra‐dinuclear metal center. Therefore, each L – ligand has a total coordination number of four but with different carboxylate modes, namely, κ 4 ‐ N, N, O, O (1, 1) in1 and κ 4 ‐ N, N, O, O′ (1, 3) in2 for the C(1)–O–C(2) group. Thus, the coordination spheres are MO2 N2 O in both cases, though1 is distorted trigonal bipyramidal, whereas2 is square pyramidal. Antiferromagnetic (AFM) coupling (17 cm –1 ) is seen only in1, though the best fit was obtained with consideration of spin–orbit coupling along with zero‐field splitting owing to exchange anisotropy. The new dinuclear nitrato species might be alternatives to previously reported mimics of enzyme active sites. Abstract : Two dinuclear compounds with the bis(3, 5‐ tert ‐butylpyrazol‐1‐yl)acetic acid anion (bd t bpza), [Co(NO3 )(bd t bpza)]2 (1 ) and [Cu(NO3 )(bd t bpza)]2 (2 ), are reported. Nitrato coligands are present instead of the commonly observed chlorido anions in dinuclear species with MO2 N2 O chromophores;1 is distorted trigonal bipyramidal, and2 is square pyramidal. Antiferromagnetic coupling is seen only in1 .